Control design via prescribed performance functions for flight management / Aufa Sirry Yashaa - Yashaa, Aufa Sirry (2019)
Flight attitude management for Unmanned Aerial Vehicles (UAV) have some difficulty in automatic control. The problem is driven by the nonlinear and uncertain nature of UAV dynamics. Controllers form the core of most of our modern technology. They allow us to achieve accurate responses from many systems simply by reference to a given signal, and automatically adjusting for any interference. The most widely used controller in industry today are the so called Proportional, Integral, Derivative controller, or PID. A simple controller featuring little parameters to tune while still achieving great performance. This performance however is only achievable provided proper tuning of the controller. A fairly recent development in controller theory is the so called Prescribed Performance Controller. First proposed by Bechlioulis and Rovithakis, the PPC is capable of achieving quick and accurate responses through the use of a performance function that defines boundary limits for error evolution. While individually these PID and PPC controllers have great performance potential, this study proposes that combining the two, forming a new hybrid PPCPID controller can achieve even better.